2003
DOI: 10.1038/nn1073
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor regulates energy balance downstream of melanocortin-4 receptor

Abstract: The melanocortin-4 receptor (MC4R) is critically involved in regulating energy balance, and obesity has been observed in mice with mutations in the gene for brain-derived neurotrophic factor (BDNF). Here we report that BDNF is expressed at high levels in the ventromedial hypothalamus (VMH) where its expression is regulated by nutritional state and by MC4R signaling. In addition, similar to MC4R mutants, mouse mutants that expresses the BDNF receptor TrkB at a quarter of the normal amount showed hyperphagia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
717
5
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 786 publications
(769 citation statements)
references
References 45 publications
20
717
5
14
Order By: Relevance
“…Role m In satiety; m water reward (Horger et al, 1999;Kernie et al, 2000;Nakagawa et al, 2003); improvement in glucose metabolism (Tonra et al, 1999;Nakagawa et al, 2000;Ono et al, 2000) m Drug reward (Horger et al, 1999) K BDNF in mesolimbic pathways regulates appetitive behavior (Eisch et al, 2003;Itoh et al, 2004); BDNF within hypothalamus regulates energy balance by enhancing catabolic processes (Xu et al, 2003) K BDNF may play a role in behavioral sensitization to drugs (Guillin et al, 2001) and potentially to palatable food via its dopaminergic and opioidergic (Siuciak et al, 1994;Siuciak et al, 1995) effects Repeated exposure kIn the hippocampus (Molteni et al, 2002;Molteni et al, 2004) m In mesocorticolimbic areas including, hypothalamus (Meredith et al, 2002;Butovsky et al, 2005); m and upregulation of BDNF receptors during withdrawal (Toda et al, 2002;Grimm et al, 2003); incubation of drug craving, accompanied by m in BDNF (Grimm et al, 2003) BDNF gene knockout animals m In food intake and obesity (Lyons et al, 1999;Kernie et al, 2000;Rios et al, 2001;Xu et al, 2003) k Drug reward (Hall et al, 2003;Horger et al, 1999) Orexin m Food intake (Edwards et al, 1999;Harris et al, 2005) Relapse to drug seeking behavior (Harris et al, 2005) Activated by SGAs ( Ibanez-Rojo et al, 1993;Bencherif et al, 2005) are available, though, to extend preclinical palatable food opioid findings to humans. Neuroimaging studies in obese people reported in...…”
Section: Bdnfmentioning
confidence: 99%
See 2 more Smart Citations
“…Role m In satiety; m water reward (Horger et al, 1999;Kernie et al, 2000;Nakagawa et al, 2003); improvement in glucose metabolism (Tonra et al, 1999;Nakagawa et al, 2000;Ono et al, 2000) m Drug reward (Horger et al, 1999) K BDNF in mesolimbic pathways regulates appetitive behavior (Eisch et al, 2003;Itoh et al, 2004); BDNF within hypothalamus regulates energy balance by enhancing catabolic processes (Xu et al, 2003) K BDNF may play a role in behavioral sensitization to drugs (Guillin et al, 2001) and potentially to palatable food via its dopaminergic and opioidergic (Siuciak et al, 1994;Siuciak et al, 1995) effects Repeated exposure kIn the hippocampus (Molteni et al, 2002;Molteni et al, 2004) m In mesocorticolimbic areas including, hypothalamus (Meredith et al, 2002;Butovsky et al, 2005); m and upregulation of BDNF receptors during withdrawal (Toda et al, 2002;Grimm et al, 2003); incubation of drug craving, accompanied by m in BDNF (Grimm et al, 2003) BDNF gene knockout animals m In food intake and obesity (Lyons et al, 1999;Kernie et al, 2000;Rios et al, 2001;Xu et al, 2003) k Drug reward (Hall et al, 2003;Horger et al, 1999) Orexin m Food intake (Edwards et al, 1999;Harris et al, 2005) Relapse to drug seeking behavior (Harris et al, 2005) Activated by SGAs ( Ibanez-Rojo et al, 1993;Bencherif et al, 2005) are available, though, to extend preclinical palatable food opioid findings to humans. Neuroimaging studies in obese people reported in...…”
Section: Bdnfmentioning
confidence: 99%
“…In mesolimbic dopaminergic pathways, BDNF regulates appetitive behavior (Eisch et al, 2003;Itoh et al, 2004) along with behavioral sensitization to drugs (Guillin et al, 2001) and potentially to palatable food. Through its hypothalamic effects, BDNF controls energy balance by enhancing catabolic processes (Xu et al, 2003). Similarly important are the actions of orexin neurons, situated in the LH and projecting to the NAc and VTA , to control food intake (Edwards et al, 1999;Harris et al, 2005) as well as drug reward and craving (Harris et al, 2005).…”
Section: Bdnfmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF exerts hypophagic and weight-reducing effects similar to MC4 receptor agonism with α-MSH or synthetic analogues such as MTII (Xu et al, 2003). Melanocortin signaling may mediate effects via the BDNF system, because acute intracerebroventricular injection of MTII led to increased BDNF mRNA expression in the VMH of fasted mice (Xu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, profound obesity has been associated with a balanced translocation that disrupts the SIM1 gene (21). Decreased expression of the brain-derived neurotropic factor (BDNF) was reported to affect eating behaviour (22). BDNF and the neurotropic tyrosine kinase receptor B are expressed in the ventromedial hypothalamus and may be downstream effectors of MC4R signalling.…”
Section: Cjc Symposium 2006mentioning
confidence: 99%